2022
DOI: 10.3390/atmos13050653
|View full text |Cite
|
Sign up to set email alerts
|

Mesoscale Horizontal Kinetic Energy Spectra of an Eastward-Moving Southwest Vortex

Abstract: A high-resolution simulation with the Weather Research and Forecasting (WRF) model is performed to investigate the characteristics of the horizontal kinetic energy (HKE) spectra of an eastward-moving southwest vortex (SWV) generated in Sichuan Province, China, during 16–19 June 2011. The results indicate that the evolution of the SWV can be divided into the development, mature, and decay stages. In the troposphere, the HKE spectrum reproduces the typical atmospheric spectrum, with a slope of approximately −3 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…However, differences of the slopes at different wavelength bands exist objectively. A large number of observational facts confirm that the spectral energy of wind displays spectral segments of a −3 slope at the synoptic scale and a −5/3 slope at the meso-scale over wavelengths of <500 km [42][43][44][45][46][47]. Moreover, the wind spectra show a transition characteristic, from dependence at a large-scale range to dependence at a meso-scale range [43,[47][48][49][50].…”
Section: The Spectral Analysis Of Terrain Precipitation and Wind Fieldmentioning
confidence: 89%
See 3 more Smart Citations
“…However, differences of the slopes at different wavelength bands exist objectively. A large number of observational facts confirm that the spectral energy of wind displays spectral segments of a −3 slope at the synoptic scale and a −5/3 slope at the meso-scale over wavelengths of <500 km [42][43][44][45][46][47]. Moreover, the wind spectra show a transition characteristic, from dependence at a large-scale range to dependence at a meso-scale range [43,[47][48][49][50].…”
Section: The Spectral Analysis Of Terrain Precipitation and Wind Fieldmentioning
confidence: 89%
“…A large number of observational facts confirm that the spectral energy of wind displays spectral segments of a −3 slope at the synoptic scale and a −5/3 slope at the meso-scale over wavelengths of <500 km [42][43][44][45][46][47]. Moreover, the wind spectra show a transition characteristic, from dependence at a large-scale range to dependence at a meso-scale range [43,[47][48][49][50]. For example, Yu et al [47] suggested that the average scale of spectral transition is around 300 km when investigating the characteristics of the horizontal Further insight into the total precipitation spectral variance (dashed line in Figure 8) and wind spectral variance (dotted line in Figure 8) is gained.…”
Section: The Spectral Analysis Of Terrain Precipitation and Wind Fieldmentioning
confidence: 97%
See 2 more Smart Citations